The effect of Lactiplantibacillus plantarum fermentation and blanching on microbial population, nutrients, anti-nutrients and antioxidant properties of fresh and dried mature Moringa oleifera leaves - Saima Perveen; Saeed Akhtar; Muhammad Qamar; Wisha Saeed; Raheel Suleman; Muhammad Younis; Tariq Ismail; Tuba Esatbeyoglu (Journal of Agriculture and Food Research)
Moringa oleifera is an excellent source of nutrients and functional ingredients of human health significance. This study was conducted to determine the role of lactic acid fermentation and blanching in improving nutritional attributes and functional properties of M. oleifera leaves. Submerged lactic acid fermentation of M. oleifera was carried out for 24 h by using a Lactiplantibacillus plantarum strain. The results showed that fermentation resulted in a microbial population of M. oleifera leaves dominated with higher count of L. plantarum i.e., 4.06 log10 CFU/g after 24 h fermentation. L. plantarum count was reduced from 4.06 to 1.61 log10 CFU/g in fermented M.oleifera leaves powder after cabinet dehydration. Higher levels of protein (29.87 %), and fiber (32.26 %) were observed in fermented M. oleifera leaves while the levels of carbohydrates (10.74 %), fat (7.72 %), and energy (232.06 kcal) were lower than the levels observed in raw and blanched leaves. Lactic acid fermentation also anticipated reduction in anthocyanin (14.50–10.37 mg/100g), chlorophyll A (52.64–45.35 mg/100g), and lycopene (11.94–9.13 mg/100g) content of M. oleifera leaves. Fermentation significantly (p ≤ 0.05) increased level of total phenolic content i.e., 55.48 mg gallic acid equivalents (GAE)/g, total flavonoid contents i.e., 70.81 mg quercetin equivalent (QE)/g and flavonols i.e., 36.97 mg QE/g. Lactic acid fermentation reduced the levels of intrinsic nutrient inhibitors such as alkaloids (2.74–1.94 g/100g; 29 % ↓), saponins (3.80–2.98 g/100g: 20 % ↓), oxalates (2.43–1.85 g/100g; 24 % ↓), tannin (0.83–0.44 g/100g; 47 % ↓), and phytic acid (1.94–1.02 g/100g; 47 % ↓) compared with the raw leaves. The results suggest lactic acid fermentation is a cost-effective technique to improve nutritional and health perspectives of M. oleifera leaves.